Pulmonary surfactant protein SP‐B promotes exocytosis of lamellar bodies in alveolar type II cells. Issue 8 (15th March 2018) - Martínez‐Calle, Marta; Olmeda, Bárbara; Dietl, Paul; Frick, Manfred; Pérez‐Gil, Jesús
Abstract : The release of pulmonary surfactant by alveolar type II (ATII) cells is essential for lowering surface tension at the respiratory air‐liquid interface, stabilizing the lungs against physical forces tending to alveolar collapse. Hydrophobic surfactant protein (SP)‐B ensures the proper packing of newly synthesized surfactant particles, promotes the formation of the surface active film at the alveolar air‐liquid interface and maintains its proper structure along the respiratory dynamics. We report that membrane‐associated SP‐B efficiently induces secretion of pulmonary surfactant by ATII cells, at the same level as potent secretagogues such as ATP. The presence in the extracellular medium of lipid‐protein complexes containing SP‐B activates the P2Y2 purinergic signaling pathway that ultimately triggers exocytosis of lamellar bodies by ATII cells. Our data suggest that SP‐B prompts Ca 2+ ‐dependent surfactant secretion via ATP release from ATII cells. This result implies that SP‐B is not only an essential component for the biophysical function of surfactant but is also a central element in the alveolar homeostasis by eliciting autocrine and paracrine cell stimulation.—Martínez‐Calle, M., Olmeda, B., Dietl, P., Frick, M., Pérez‐Gil, J. Pulmonary surfactant protein SP‐B promotes exocytosis of lamellar bodies in alveolar type II cells. FASEB J . 32, 4600‐4611 (2018). www.fasebj.org